(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2006)
Biometric parameters of pollen of some sorts of grapes growing in zone of ANPP and in the control - Merdzavan are investigated. Comparative analysis demonstrate the high quality of researched parameters for investigated genotypes in both points of their growth. The pollen population with genotypes of optimal parameters (Burmunk, Arakseni, Ararati) can be applied as a material for bioindication and selection.